Maternal nutrients and 15N Leucine tracing in Sebastes schlegelii - Du, Tengfei; Xiao, Yongshuang; Liu, Qinghua; Guo, Teng; Gao, Guang; Li, Jun (Frontiers in Marine Science, 2022)
Sebastes schlegelii is a commercially important fishery resource that is also a representative viviparous fish species in the Northeast Asian Sea. The mode of nutritional supply of embryos fertilized and developed in vivo is not clear. To screen biomarkers for nutrient transfer between mother and embryo, we studied the composition of and changes in maternal blood at different developmental stages. The results showed that the blood of S. schlegelii was rich in nutrients, including 16 hydrolysed amino acids, 20 fatty acids, glucose and fructose. The contents of amino acids in the blood reached 3.44-4.58 g/100 g, which is approximately 3-5 times that of fatty acids and 44-155 times that of sugar. Thirteen amino acids, 15 fatty acids and glucose showed an increasing trend in the early stage of embryonic development and a decreasing trend in the later stage. The contents of leucine, as an essential amino acid in early development, changed significantly in maternal blood and was therefore selected as a biomarker. The results of isotope labelling showed that 15N leucine was not detected in the eggs, gastrula embryos or organogenesis embryos, but a high abundance of 14N leucine was detected in the eggs and embryos of the control and experimental groups, indicating that leucine, an essential amino acid for aquatic animals, plays an important role in gamete and embryo development. An abundance in 15N-labelled leucine was detected in the embryonic blood and ovarian villi but not in the embryos, which indicates that the ample free naturally abundant leucine in maternal blood during the middle and late developmental stages of the eggs and embryos was not absorbed or utilized. These results showed that eggs and embryos had certain autonomy and selectivity when absorbing nutrients and gave priority to the active transport of certain complex macromolecular nutrients that could meet their needs for a variety of nutrients at the same time.